PROFESSIONAL TRAINING IN PHYSICAL EDUCATION: ASSESSING THE SERVICES OF ACADEMIC COMPANIES (Fiep Bulletin - online, 2017)
This article aims to present the evaluation criteria of the Professional Training course Bachelor / Degree in PhysicalEducation from the University Vila Velha considering its innovative character. This qualitative research used the portfolios assources since these are recorded descriptive reviews of the entire process, including reflections and dialogue between thoseinvolved in the teaching-learning process. The involvement of students and supervising teachers and stage supervisor allows adialectic action between universities and the labor market that goes beyond the simple to teaching.
Keywords: Professional Training; Assessment; Business Academic